Serving India : A Political Biography of Subimal Dutt (1903-1992), India's Longest Serving Foreign Secretary - Gupta, Amit Das., (Brill | Manohar Publishers & Distributors, 2017)
This is the first academic biography of Subimal Dutt, best known as India's longest serving Foreign Secretary, covering the nearly nine eventful decades of his life. It tells the story how a Bengali village boy without any connections had one of the most distinguished careers of his generation without ever forgetting his roots. Struggling all his life between professional ambition and deep spirituality, Dutt never transformed into one of those 'brown Englishmen' so typical of South Asia's civil servants, but remained a strictly impartial, straightforward and incorruptible officer of - as he formulated it himself - the 'vernacular type'. Intellect and discipline brought him into the Indian Civil Service and soon to Delhi, where he excelled as an outstanding administrator and moved into the field of foreign relations. After an interlude as Indian Agent in Malaya, as Bengal's Secretary for Agriculture he held a most important posting during the Second World War. Working closely with Nehru in his capacity as Commonwealth and later Foreign Secretary for over twelve years, he became one of the most influential advisors of India's first Prime Minister. His career seemed to come to an end as Secretary to the President and later Vigilance Commissioner, but in 1972 he was appointed India's first High Commissioner to Bangladesh, building bridges between the country of his birth and the one he had chosen in 1947. Though Dutt made it a point to be nearly invisible throughout his career, thereafter he did everything possible to be rediscovered posthumously.